Educational Objectives and Criteria for the Ideal Teacher Perspective of Plato and Al Ghazali - Cinta, Fitria; Maulana, Asep; Maskud, Maskud (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
This study aims to reflect back on educational goals and teacher criteria according to Plato and Al Ghazali. Writing this scientific paper using descriptive qualitative method through a comparative approach. Literature study is the data collection technique used and the data analysis technique used is to analyze the data or content analysis with the relevant data collection stages. The results of this study are the similarities in the educational goals of Plato's and Al-Ghazali's perspectives, both of which lead to efforts to get happiness. The educational goals of Plato's perspective put more emphasis on scientific abilities and character development so as to achieve individual and state happiness and prosperity. While the purpose of education according to al-Ghazali is an effort to form a perfect human being by getting closer to Allah so that he will get happiness in the world and the hereafter. This can be achieved through several aspects which include cognitive, affective and psychomotor aspects. The similarity of the criteria for teachers from both perspectives, namely between Plato and Al Ghazali requires teachers to always do good, be diligent in worship because teachers are role models for their students. While the difference in the criteria for teachers from Plato's and Al Ghazali's perspectives is that Plato is more inclined so that teachers are able to master several criteria that prioritize cognitive aspects and position themselves as friends. Meanwhile, Al Ghazali is more inclined for teachers to prioritize affective aspects. So that teachers are expected to have characteristics that can bring happiness to the world and the hereafter and teachers must behave like parents to children. Al Ghazali also believes that a teacher must instill sincerity, sincerity, and not demand an honorarium as a teaching assignment.